An evaluation of portion size estimation aids: precision, ease of use and likelihood of future use. Issue 13 (9th February 2016) - Faulkner, Gemma P; Livingstone, M Barbara E; Pourshahidi, L Kirsty; Spence, Michelle; Dean, Moira; O'Brien, Sinead; Gibney, Eileen R; Wallace, Julie MW; McCaffrey, Tracy A; Kerr, Maeve A
Abstract: Objective: The present study aimed to evaluate the precision, ease of use and likelihood of future use of portion size estimation aids (PSEA). Design: A range of PSEA were used to estimate the serving sizes of a range of commonly eaten foods and rated for ease of use and likelihood of future usage. Setting: For each food, participants selected their preferred PSEA from a range of options including: quantities and measures; reference objects; measuring; and indicators on food packets. These PSEA were used to serve out various foods (e.g. liquid, amorphous, and composite dishes). Ease of use and likelihood of future use were noted. The foods were weighed to determine the precision of each PSEA. Subjects: Males and females aged 18–64 years ( n 120). Results: The quantities and measures were the most precise PSEA (lowest range of weights for estimated portion sizes). However, participants preferred household measures (e.g. 200 ml disposable cup) – deemed easy to use (median rating of 5), likely to use again in future (all scored either 4 or 5 on a scale from 1='not very likely' to 5='very likely to use again') and precise (narrow range of weights for estimated portion sizes). The majority indicated they would most likely use the PSEA preparing a meal (94 %), particularly dinner (86 %) in the home (89 %; all P <0·001) for amorphous grain foods. Conclusions: Household measures may be precise, easy to use and acceptable aids for estimating the appropriate portion size of amorphous grain foods.